Industries without smokestacks in Uganda and Rwanda - John Spray; Sebastian Wolf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We use unique high-frequency Government of Uganda and Government of Rwanda tax administration datasets to map the characteristics of 'industries without smokestacks' in East Africa. First, we find firm size appears to be crucial for successful industries without smokestacks in services and agro-processing. Second, we find that firms do not need to be active in the external economy themselves to achieve high levels of productivity, but that strong links to external sector actors are more common among more productive firms. Third, all industries with high levels of labour productivity rely heavily on imported inputs, though this is more pronounced in the manufacturing sector. We then identify the role of cross-sector spillovers in economic performance. We find that all of the top ten most interconnected sectors of the economy are either in manufacturing or services. We show that growth in output and productivity in these sectors is a strong indicator of overall economic growth. Finally, we show that sales and employment spillovers from foreign direct investment are most likely to occur in the manufacturing sector.
Keywords: 330; economic growth; industry; firm size; tax administration data; Uganda; Rwanda